Sosialisasi Dampak Pernikahan Dini dalam meningkatkan Kesadaran Hukum Santriwati di Pondok Pesantren Al Kholiliyah Al Aziziyah Bangkalan - Muhammad Abdullah; Mujito Mujito; Muhammad Yusron Maulana El-Yunusi (Universitas Islam Internasional Darullughah Wadda'wah, 2025)
This community service activity aimed to improve santriwati’s legal awareness of early marriage impacts at Al Kholiliyah Al Aziziyah Islamic Boarding School, Bangkalan. Using the Participatory Action Research (PAR) method involving 15 participants, the program emphasized understanding the reproductive health, psychological, educational, and economic consequences of early marriage. Pre-test results showed limited knowledge (only 20–40% answered correctly), while post-test results demonstrated significant improvement: 93% understood reproductive health impacts, 87% psychological effects, 90% educational impacts, and 85% economic consequences. The activity also encouraged the formation of a peer group for early marriage prevention within the pesantren. These findings indicate that participatory and contextual approaches effectively enhance young women’s legal and social awareness while strengthening the role of Islamic boarding schools in preventing early marriage.